Eddy effects on surface chlorophyll in the northern South China Sea: Mechanism investigation and temporal variability analysis. (June 2016) - He, Qingyou; Zhan, Haigang; Cai, Shuqun; Li, Zimu
Abstract: The effects of eddies on surface chlorophyll (CHL) in the northern South China Sea are investigated by analyzing the long-term composite averages of CHL anomalies between 1998 and 2011 that were associated with eddies. CHL anomalies that are modulated by different dynamical processes are distinguished and discussed separately. The positive CHL anomalies within cyclonic eddies are generally larger in magnitude than the negative CHL anomalies within anticyclonic eddies, which implies a net increase in chlorophyll induced by eddy activities. At least two dynamical mechanisms, eddy pumping and eddy stirring, are found to play important roles in the CHL anomalies. The influence of eddy pumping is restricted by the mixed layer depth and its distance from deep nutriclines. Thus, the associated CHL anomalies are most apparent in winter and diminish in the following summer for both cyclonic and anticyclonic eddies. The inter-annual variation in the CHL anomalies within cyclonic eddies is modulated by the eddy intensity and exhibits a close relationship with the El Niño-Southern Oscillation. Meanwhile, the variation within anticyclonic eddies might be affected by the background CHL, with a downward trend during the study period. This work provides an overview to the nature and temporal variations in CHL anomalies that are associated with eddies in the northern South China Sea. Highlights: Eddy stirring and eddy pumping dominate the chlorophyll anomalies generated by eddies. CHL anomalies within cyclonic eddies are closely related to ENSO. CHL anomalies within anticyclonic eddies exhibit a long-term downward trend. Eddy activities contribute to chlorophyll enrichment in the northern South China Sea.